2020
DOI: 10.1177/2325967120923950
|View full text |Cite
|
Sign up to set email alerts
|

Lower Tibial Tunnel Placement in Isolated Posterior Cruciate Ligament Reconstruction: Clinical Outcomes and Quantitative Radiological Analysis of the Killer Turn

Abstract: Background: The “killer turn” effect after posterior cruciate ligament (PCL) reconstruction is a problem that can lead to graft laxity or failure. Solutions for this situation are currently lacking. Purpose: To evaluate the clinical outcomes of a modified procedure for PCL reconstruction and quantify the killer turn using 3-dimensional (3D) computed tomography (CT). Study design: Case series; Level of evidence, 4. Methods: A total of 15 patients underwent modified PCL reconstruction with the tibial aperture be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Compared to the AM tibial tunnel, the AL, L‐AM, and L‐AL tibial tunnels can significantly reduce the sharpness of the “killer turn”. 18 , 19 We hypothesized that the AM group would have better biomechanical properties than other tunnel groups. However, the experimental results did not support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the AM tibial tunnel, the AL, L‐AM, and L‐AL tibial tunnels can significantly reduce the sharpness of the “killer turn”. 18 , 19 We hypothesized that the AM group would have better biomechanical properties than other tunnel groups. However, the experimental results did not support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those in two recent studies, who reported the postoperative outcomes of the distal tibial tunnel in PCL reconstruction. 20,41 Lin et al 20 included 15 patients who underwent PCL reconstruction using distal tibial tunnel. They found that a distal tunnel significantly reduced the killer turn, but the clinical outcome was similar with that of anatomic tibial tunnel within a mean follow-up of 35.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic PCL tibial tunnel has been the most commonly used technique for transtibial PCL reconstruction. 19,20 Nevertheless, accurate placement of PCL tibial tunnel at the anatomic footprint is difficult due to the limited visualization under arthroscope. For obtaining a better arthroscopic visualization, a common mistake during surgery is placing the tibial tunnel too proximal related to the anatomic tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that the mean maximum angle of the tibial tunnel in the anteromedial approach was 58° ± 8° [26]. In previous studies on PCL reconstruction, various angles of the tibial tunnel were utilised, and angles of 45° and 60° were most commonly used by surgeons [17, 19, 28]. To our knowledge, few studies have compared the biomechanical properties of graft‐screw‐tibia constructs for different angles of the tibial tunnel in transtibial PCL reconstruction.…”
Section: Introductionmentioning
confidence: 99%